(untitled) (International Journal of Plant Biology, 2015)
This study assessed the effect of petrol and spent lubricating oil on the major growth traits (such as root length, stem length, leaf area, and biomass), and the changes in epidermal layer of leaf and its mitotic index in Guinea Corn (Sorghum bicolor L.) exposed to 0% (control), 5%, 10%, 15% and 20% concentrations of petrol and spent lubricating oil. Each concentration was mixed with 3 kg of soil in a plastic pot and each treatment was carried out in three replicates. Forty days after planting, the leaf areas of guinea corn plant were 95.83 cm2, 89.67 cm2, 89.47 cm2, and 77.80 cm2 in control, 5%, 10%, 15%, and 20% respectively of petrol pollutant. The means of stem length were 32.50±0.5 cm, 22.60±0.65 cm, 21.27±0.75 cm, 20.83±0.28 cm and 20.33±0.28 cm in control, 5%, 10%, 15% and 20% respectively. Both leaf area and stem length of treated seedlings reduced with increased concentration of the pollutants. Additionally, reduction in the dry weight of the seedlings increased with increasing concentration of both petrol and spent oil. The micrograph of the internal anatomy of the upper epidermal layers of the leaf revealed broken and scattered epidermal cells and smaller sizes of the stomata, and were increased with the increasing concentration of the treatment. Statistical analysis of the treatment shows that there was a significant reduction (P<0.05) in the stem length and leaf area of the seedlings. This study revealed that petroleum pollutant adversely affected germination, growth and development of guinea corn but petroleum products like spent oil can provide nutrition necessary for growth and yield of plant at low concentration.